Remote control of Autonomous Robots via Internet - Sugisaka, M.; Mohamed Rizon, Mohamed Juhari (King Mongkut’s Institute of Technology Ladkrabang (KMITL), 2009)
Organized by Research Center for Communications and Information Technology (ReCCIT), KMITL, 25th - 27th August 2004 at The Shangri-La Hotel, Bangkok, Thailand.